Multipotent mesenchymal stromal cells are fully permissive for human cytomegalovirus infection - Qiao, Guan-Hua; Zhao, Fei; Cheng, Shuang; Luo, Min-Hua (Virologica Sinica, 2016)
Congenital human cytomegalovirus（HCMV） infection is a leading infectious cause of birth defects.Previous studies have reported birth defects with multiple organ maldevelopment in congenital HCMV-infected neonates. Multipotent mesenchymal stromal cells（MSCs） are a group of stem/progenitor cells that are multi-potent and can self-renew, and they play a vital role in multiorgan formation. Whether MSCs are susceptible to HCMV infection is unclear. In this study, MSCs were isolated from Wharton＇s jelly of the human umbilical cord and identified by their plastic adherence, surface marker pattern, and differentiation capacity. Then, the MSCs were infected with the HCMV Towne strain, and infection status was assessed via determination of viral entry,replication initiation, viral protein expression, and infectious virion release using western blotting,immunofluorescence assays, and plaque forming assays. The results indicate that the isolated MSCs were fully permissive for HCMV infection and provide a preliminary basis for understanding the pathogenesis of HCMV infection in non-nervous system diseases, including multi-organ malformation during fetal development.